Sustainable Development Goal 11 and a New Urban Agenda for Caribbean Small Island Developing States: Policy, Practice, and Action - Mycoo, Michelle A.; Bharath, Keisha (Frontiers in Sustainable Cities, 2021)
Many Anglophone Caribbean Small Island Developing States face the daunting task of fulfilling the United Nations Sustainable Development Goals within a timeframe of the next ten years. As signatories to the United Nations Sustainable Development Goals, their governments committed to embark on a roadmap to achieve sustainable development. In this context, Anglophone Caribbean Small Island Developing States have embraced Sustainable Development Goal 11 in pursuit of creating inclusive, safe, resilient and sustainable cities as articulated in various governance, spatial, socio-economic and environmental policies. However, a tension exists between policy and practice. Several barriers to policy implementation have stymied efforts to make progress in fulfilling Goal 11 over the last five years. Enabling the impact of sound policy through well-informed practice is pivotal, if these states are to make advancements in ensuring that their population has access to basic services and live in safe, resilient and sustainable cities without leaving any citizen behind. This paper firstly seeks to critically review existing policies and practice that impact on the attainment of Sustainable Development Goal 11. It highlights the drivers of unsustainable urbanisation that are undermining progress in achieving this key sustainable development goal. In keeping with the United Nations declaration of a Decade for Action, this paper secondly makes recommendations for action that are fundamental to putting Anglophone Caribbean Small Island Developing States on a trajectory leading to the fulfilment of Goal 11. It specifically recommends strategic actions within the context of a New Urban Agenda that is relevant to Anglophone Caribbean Small Island Developing States. The experience of Trinidad is drawn upon to provide a narrative of gaps between policy and practice, and to distil key actions for attaining SDG 11 by 2030 and beyond.